Hollow palladium–copper bimetallic nanospheres with high oxygen reduction activity. (10th September 2015) - An, Lijuan; Zhu, Mingyuan; Dai, Bin; Yu, Feng
Abstract: Hollow PdCu nanospheres were synthesized via a soft template method using tetrabutylphosphonium bromide (Bu4 PBr) as a surfactant in an aqueous medium. The catalytic activity of the hollow PdCu nanospheres can be adjusted by changing the catalyst composition. TEM and HAADF STEM show that the synthesized PdCu nanospheres have hollow spherical structures and that both Pd and Cu are relatively uniformly distributed. Compared to commercial Pd/C or Pt/C catalysts, the synthesized PdCu/C materials exhibit a higher electrocatalytic activity for the oxygen reduction reaction in 0.1 mol L −1 NaOH solution. The results indicate that the hollow PdCu/C structures are promising electrocatalysts for cathodic electrodes used in alkaline conditions. The enhanced properties of the hollow PdCu/C catalyst are mainly due to the synergy of Cu dopants and the hollow porous structure.